Perlindungan Hukum Terhadap Notaris Pengganti Terkait Pemanggilan Dirinya Atas Akta Yang Dibuatnya Terlibat Dalam Proses Peradilan - Rahmayanthi, Gayatri; Darmadi, Anak Agung Ngurah Oka Yudistira (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 03 (2024)DO - 10.24843/AC.2024.v09.i03.p10, 2024)
The purpose of writing this article is to understand the responsibilities of a Substitute Notary and to find out the legal protection for the Substitute Notary for his/her summons regarding Deed Products made while carrying out his or her position involved in the Judicial Process. This research examines the unclear norms of Article 65 UUJN regarding the responsibilities and legal protection for Substitute Notaries when serving as witnesses to disputed deeds, using normative legal research methods as well as conceptual and statutory approaches. The research results show that a Substitute Notary has the same responsibilities and obligations as a Notary, including the obligation to keep the deed confidential and the right to deny. However, there is no explicit legal protection for Substitute Notaries regarding summoning as witnesses in the judicial process. Article 66 UUJN does not clearly state the right of refusal for Substitute Notaries, so protection for them is still inadequate, especially considering their limited experience. Therefore, it is necessary to reconstruct norms to overcome this ambiguity and provide clearer and firmer legal protection for Substitute Notaries.